Overcoming water scarcity and quality constraints: Recognizing Water Rights - von Benda-Beckmann, Franz and Keebet (International Food Policy Research Institute, 2001)
The time when water could be freely used without being subject to legal rights and obligations is past. Because of population growth, industrial and agricultural development, and new water technologies, water has become increasingly scarce.